AB100. Laparoscopic ureteral reimplantation underneath broad ligament tunnel for female vesicoureteral stenosis: a technical innovation - Xu, Chuanliang (Transl Androl Urol, 2014)
PURPOSE: In order to anatomically reconstruct the ureteral stenosis, we present a novel technique for laparoscopic ureteral reimplantation. PATIENTS AND METHODS: Three young females, who were diagnosed as hydroureteronephrosis caused by congenital vesicoureteral junction obstruction, were treated by laparoscopic ureteral reimplantation with a tunnel underneath the broad ligament. RESULTS: Surgery was performed successfully without conversion to open surgery. No major intraoperative or postoperative complications occurred. The mean postoperative follow-up was 38, 33 and 26 months respectively. The operative time was between 220 and 260 minutes. The mean estimated blood loss was less than 20 mL. Subsequent imaging performed 3 months after surgery revealed relief of hydroureteronephrosis for all patients. Patients all gave birth to healthy neonates and showed normal urinary tract sonogram and urine analysis during gestation period. CONCLUSION: Laparoscopic ureteral reimplantation with a tunnel underneath the broad ligament tunnel is safe, effective, allowing for anatomical reconstruction of ureter defects, however. A larger clinical sample and longer follow-up period will be needed for fully validation of this technique.